Academic Motivation Scale: Development, Application and Validation for Portuguese Accounting and Marketing Undergraduate Students - Silva, Rui (2019)
Submitted by Ricardo Rodrigues (rjagr@ubi.pt) on 2019-01-19T19:05:30Z No. of bitstreams: 1 Silva, Rodrigues, Leal - 2018 - Academic Motivation Scale Development, Application and Validation for Portuguese Accounting and Marketin.pdf: 596227 bytes, checksum: e923292b824adab2d879a514eed2a513 (MD5)